2012
DOI: 10.1254/jphs.11r04cr
|View full text |Cite
|
Sign up to set email alerts
|

Ischemic Stroke and Glucose Intolerance: a Review of the Evidence and Exploration of Novel Therapeutic Targets

Abstract: Abstract. Stroke is one of the leading causes of death and disability worldwide. It is well known that hyperglycemia and/or diabetes potentially exacerbate the neuronal damage observed following ischemic stroke. Recent reports have shown that hyperglycemia/glucose intolerance may be induced by cerebral ischemic stress, and that normalization of blood glucose levels during the first 48 h of hospitalization appears to confer greater survival outcomes in stroke patients. However, the mechanisms underlying post-is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(29 citation statements)
references
References 103 publications
(97 reference statements)
1
27
0
Order By: Relevance
“…In contrast, the administration of intravenous insulin with the objective of maintaining serum glucose within a specific range in the first hours of acute ischemic stroke 1) does not provide benefit in terms of functional outcome, death, or improvement in final neurologic deficit and 2) significantly increased the number of hypoglycemic episodes (Bellolio et al, 2011), suggesting the need for ongoing discussion about the importance of postischemic glucose metabolism regulation. We recently reported that focal cerebral ischemia per se causes a hyperglycemic condition (i.e., postischemic glucose intolerance) and that this may worsen the ischemic neuronal damage in mice (Harada et al, 2009a(Harada et al, , 2012b.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, the administration of intravenous insulin with the objective of maintaining serum glucose within a specific range in the first hours of acute ischemic stroke 1) does not provide benefit in terms of functional outcome, death, or improvement in final neurologic deficit and 2) significantly increased the number of hypoglycemic episodes (Bellolio et al, 2011), suggesting the need for ongoing discussion about the importance of postischemic glucose metabolism regulation. We recently reported that focal cerebral ischemia per se causes a hyperglycemic condition (i.e., postischemic glucose intolerance) and that this may worsen the ischemic neuronal damage in mice (Harada et al, 2009a(Harada et al, , 2012b.…”
Section: Introductionmentioning
confidence: 99%
“…This release results in insulin resistance, glycogenolysis, gluconeogenesis, proteolysis and lipolysis [29,30]. Furthermore, there is substantial evidence that stroke can induce hyperglycemia indirectly by activation of an inflammatory reaction [29,30,31]. …”
Section: Pathophysiology Of Prediabetes After Strokementioning
confidence: 99%
“…Patients with both impaired fasting glucose and impaired glucose tolerance show both hepatic and muscle insulin resistance and decreased both early- and late-phase insulin responses to oral glucose, which might explain the higher risk in these patients to develop diabetes compared with patients with impaired fasting glucose or impaired glucose tolerance alone [26,32]. There is evidence that insulin sensitivity is impaired after ischemic stroke, possibly due to decreased hepatic insulin receptor expression and upregulation of gluconeogenesis, which can lead to impaired glucose tolerance [31]. …”
Section: Pathophysiology Of Prediabetes After Strokementioning
confidence: 99%
“…As neurons require a constant supply of glucose for normal function, glucose is a major source of energy metabolism for the central nervous system (39). Several studies have documented the effect of glucose-sensing neuropeptides on the development of post-ischemic glucose dysfunction and neuronal damage (22,23), and evidence from a previous in vitro study revealed that glucose itself promotes the development of caspase-dependent apoptosis during re-oxygenation following oxygen and glucose deprivation, and promotes the production of reactive oxygen species, including superoxide anion, hydrogen peroxide and peroxynitrite (40). GK and GKRP have important regulatory roles in glucose metabolism as a glucose sensor.…”
Section: Time Following Ischemia-reperfusion ------------------------mentioning
confidence: 99%